The State of Information and Communication Technology in Hungary – A Comparative Analysis - Peter Sasvari (Informatica, 2011)
A novel comparative research and analysis method is proposed and applied on the Hungarian economic sectors. The question of what factors have an effect on their net income is essential for enterprises. First, the potential indicators related to economic sectors were studied and then compared to the net income of the surveyed enterprises. The data resulting from the comparison showed that the growing penetration of electronic marketpalces contributed to the change of the net income of enterprises in various economic sectors to the extent of 37%. Among all the potential indicators, only the indicator of electronic marketplaces has a direct influence on the net income of enterprises. Two clusters based on the potential indicators were indicated.
Keywords: M13; M15; 330; information society; economic sector; electronic presence; electronic marketplace; ICT